Unit type curtain wall annular track hoisting device and design method thereof - WEI HAIFANG; LUO JIZHEN; MO TINGHUI; TAN LINFANG; CAI NA; WANG AN; LIN SHAN; LI FUKUN; TANG WENCHENG; LING RANSHENG (2024)
The invention provides a unit type curtain wall annular track hoisting device and a design method thereof, and belongs to the technical field of unit type curtain wall hoisting, the unit type curtain wall annular track hoisting device comprises a support frame fixing piece, a support frame vertical rod, a support frame cross beam, a support frame inclined rod, a support frame longitudinal beam, track I-shaped steel, a traction rope, a pull ring, a ground ring and an electric hoist. The unit type curtain wall hoisting device is simple in structural principle, assembling and hoisting operation are very convenient, the hoisting height and the mounting position of a unit type curtain wall can be flexibly adjusted, the unit type curtain wall is hoisted to a preset position, the curtain wall hoisting operation efficiency is higher, and the construction efficiency is guaranteed. 本发明提供一种单元式幕墙环形轨道吊装装置及其设计方法，属于单元式幕墙吊装技术领域，包括支撑架固定件、支撑架立杆、支撑架横梁、支撑架斜杆、支撑架纵梁、轨道工字钢、牵拉绳、拉环、地环和电动葫芦。本发明结构原理简单，组装装置、吊装作业都很方便，可灵活的调整单元式幕墙的吊装高度和安装位